Assessing the Effectiveness of the Desa Prima Program in Empowering Women Economically - Prasetyo, Joni; Komariah, Kokom (Departement of Nonformal Education, Graduate Scholl of Universitas Negeri Yogyakarta, 2025)
This study aims to evaluate the implementation of the Desa Prima Program as a form of productive economic empowerment for women in Wedomartani Village, Sleman Regency, using the CIPP evaluation model (Context, Input, Process, Product). The research was conducted over three months, from October 2024 to January 2025. It was aligned with the program’s schedule to ensure the collected data would be both representative and current. The research subjects included 28 women who were active participants in the Desa Prima Program and program administrators who served as key informants. This study employed a formative evaluation design using a mixed-methods approach, combining qualitative methods (in-depth interviews, observations, and documentation) with quantitative methods (questionnaires). The research instruments were developed based on the indicators of the CIPP model and were validated through expert judgement and source triangulation. Qualitative data were analyzed thematically, while quantitative data were analyzed using descriptive statistics based on a Likert scale to determine the mean scores and percentages for each evaluation aspect. The results show that, in terms of context, the program was deemed highly relevant to women’s economic needs (84.8%), with the majority of participants having no prior income (80.4%). Regarding input, the training facilities were considered adequate (81.3%), and the participant selection process was viewed as fair (82.1%), although the distribution of tools and availability of mentoring remained limited. In the process aspect, the training was participatory, with facilitator attendance rated relatively high (79.5%) and mentoring experienced by 77.7% of participants; however, a formal evaluation system was lacking. In terms of product, 60.7% of participants reported an increase in income, 57.1% continued to run their businesses, and all participants (100%) expressed a desire for the program to continue. The program has shown early positive impacts in promoting women’s economic independence, although further institutional strengthening, legal business access, and cross-sectoral sustainability strategies are still needed. Keywords: women empowerment, evaluation, Desa Prima, productive economy, CIPP model